2011
DOI: 10.2298/gensr1102331m
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of phenotypic diversity of apple (Malus sp.) germplasm through the principle component analysis

Abstract: A wide range of apple cultivars representing Malus sp. germplasm were collected from southern part of Serbia, where this specie has been in cultivation for a long time. Data for twelve traits were collected for 18 cultivars for three consecutive years. Cultivars differed in phenology, fruit weight, yield and chemical composition were evaluated. Correlations were identified among phenological and compositional traits. Principal component analysis (PCA) was performed to study correlation among variables in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 12 publications
2
9
0
Order By: Relevance
“…Fruit weight ranged from 47.53 ± 5.38g in American Trel to 253.96 ± 47.12g in "Lal Ambri". Similar variations in fruit weight ranging between 70g to 193.33g have been reported by Mratinic and Aksic (2011) for some local cultivars of apple in South Serbia. Pirlak et al (2003) also reported significant variations for fruit weight among some local apple cultivars ranging between 49.5g and 152.2g.…”
Section: Biosystematic Characterization Of Apple Germplasm Of Kashmir Valley 41supporting
confidence: 83%
“…Fruit weight ranged from 47.53 ± 5.38g in American Trel to 253.96 ± 47.12g in "Lal Ambri". Similar variations in fruit weight ranging between 70g to 193.33g have been reported by Mratinic and Aksic (2011) for some local cultivars of apple in South Serbia. Pirlak et al (2003) also reported significant variations for fruit weight among some local apple cultivars ranging between 49.5g and 152.2g.…”
Section: Biosystematic Characterization Of Apple Germplasm Of Kashmir Valley 41supporting
confidence: 83%
“…Globalization and standardization in the Serbian apple market have drastically reduced the numbers of autochthon cultivars and most of them have nearly disappeared; however, some of these cultivars, such as Petrovača, Budimka, Kolačara Pozna, and Kožara, have extraordinary quality, good pomological characteristics, and pest and disease resistance (Mratinić, 2005 ; Mratinić and Fotirić Akšić, 2011 , 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Principal component analysis (PCA) has been used previously in many studies to evaluate germplasm of apple, and our results were in agreement with Pereira-Lorenzo et al (2003) findings regarding characterization of 89 morphological characters of 408 apple accessions using, the PCA revealed six main sources of variability in the following order: size of fruit, color of skin, acidity and sweetness. Mratinic and FotricAksic (2011) found that the first three components accounted for 65% of the total variable traits among 18 apple cultivars using 12 morphological characters.…”
Section: Principal Component Analysis (Pca)mentioning
confidence: 99%